Epidemiological risk factors for animal influenza A viruses overcoming species barriers - Harris, K.A.; Freidl, G.S.; Muñoz, O.S.; Dobschuetz, S. von; Nardi, M. de; Wieland, Barbara; Koopmans, M.P.G.; Stärk, K.D.C.; Reeth, K. van; Dauphin, G.; Meijer, A.; Bruin, E. de; et al. (Springer, 2017)
Drivers and risk factors for Influenza A virus transmission across species barriers are poorly understood, despite the ever present threat to human and animal health potentially on a pandemic scale. Here we review the published evidence for epidemiological risk factors associated with influenza viruses transmitting between animal species and from animals to humans. A total of 39 papers were found with evidence of epidemiological risk factors for influenza virus transmission from animals to humans; 18 of which had some statistical measure associated with the transmission of a virus. Circumstantial or observational evidence of risk factors for transmission between animal species was found in 21 papers, including proximity to infected animals, ingestion of infected material and potential association with a species known to carry influenza virus. Only three publications were found which presented a statistical measure of an epidemiological risk factor for the transmission of influenza between animal species. This review has identified a significant gap in knowledge regarding epidemiological risk factors for the transmission of influenza viruses between animal species.